1994
DOI: 10.1111/j.1545-5300.1994.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Physical Violence in Couple Therapy: Methodological, Practical, and Ethical Considerations

Abstract: Over two-thirds of clients in family therapy clinics engage in some form of physical violence against their partners within the year prior to the initiation of therapy. However, family therapists are aware of only a small proportion of these cases. The purpose of this article is to enhance the ability of family therapists to detect marital violence. We examine client and therapist reasons for why physical violence is not detected. We then review various methods to screen for the presence of physical violence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 37 publications
0
48
0
3
Order By: Relevance
“…This is better than would be expected based on the previous research in this area. Many of the former studies report that clinicians do not do a good job of recognizing partner violence in their clients (Aldarondo & Straus, 1994;Avis, 1992;Goodstein & Page, 1981;O'Leary, Vivian, & Malone, 1992;Stith, 2000).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This is better than would be expected based on the previous research in this area. Many of the former studies report that clinicians do not do a good job of recognizing partner violence in their clients (Aldarondo & Straus, 1994;Avis, 1992;Goodstein & Page, 1981;O'Leary, Vivian, & Malone, 1992;Stith, 2000).…”
Section: Discussionmentioning
confidence: 94%
“…It is likely to result in health problems, stress, depression, divorce, injury, or even death (Sitterding, 2003). Therefore, further research into this phenomenon is warranted (Aldarondo & Straus, 1994;Hansen, Harway, & Cervantes, 1991;Stith, Smith, Penn, Ward, & Tritt, 2003;Strawderman, Rosen, & Coleman, 1997).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In North America, millions of women are presently being exposed to physical, psychological, emotional, sexual, and financial forms of abuse (Sudermann & Jaffe, 1999). Aldarondo and Straus (1994) and O'Leary, Vivian and Malone (1992) reported that over two-thirds of clients who are in family therapy have engaged in some type of violence against their partner within one year of commencing the therapy. Johnson and Lebow (2000) reported that domestic violence statistics, even taken within family therapy settings, are typically an underestimate, due to many people being afraid to report the violence.…”
Section: Introductionmentioning
confidence: 96%
“…Researchers are beginning to assess the costs of domestic violence -economic, psychological and socialand note that a high proportion of victims of child maltreatment end up in the mental health system as adults (Ammerman and Hersen, 1999). Aldarondo and Straus (1994) estimated that two-thirds of clients in couples/family meetings engaged in physical violence against their partners in the year prior to the initiation of therapy. Ehrensaft and Vivian (1996) found that of 60% of couples seeking therapy who had experienced physical violence, only 10% spontaneously reported the violence.…”
Section: Introductionmentioning
confidence: 99%